Show me a story - 40 craft projects and activities to spark childrens story. - Neuburger, Emily K., ....- (Storey Publishing Llc, 2012)
Encouraging children to let their imagination run wild, Emily K. Neuburger offers 40 inventive projects and activities that will inspire kids ages 5 to 12 to express themselves through storytelling. Younger children will love making story stones and a storytelling jar, while older kids will open up and thrive as they embark on guided story walks and inspiring journaling exercises. Sparking creativity while developing a child's love of language, Show Me a Story will kindle a lifelong passion for both writing and telling original stories. Emily K. Neuburger moedigt kinderen aan hun fantasie de vrije loop te laten en biedt 40 inventieve projecten en activiteiten die kinderen van 5 tot 12 jaar zullen inspireren zich te uiten door middel van verhalen. Jongere kinderen zullen dol zijn op het maken van verhaalstenen en een vertelpot, terwijl oudere kinderen zich openstellen en opbloeien tijdens begeleide verhalenwandelingen en inspirerende dagboekoefeningen. Show Me a Story stimuleert de creativiteit en ontwikkelt de liefde voor taal. Het zal een levenslange passie opwekken voor het schrijven en vertellen van originele verhalen.
Keywords: Actief met kinderen; Kleuteronderwijs; Knutselen met kinderen; Lager onderwijs; Taalontwikkeling